Modifying the Complex Refractive Index of Thin-Films for Nanooptical Applications - Kunne, Marco; Kusserow, Thomas; Witzigmann, Bernd; Hillmer, Hartmut (2024 International Conference on Optical MEMS and Nanophotonics (OMN), 2024)
We present a method to generate 2D refractive index patterns in thin-films for nanooptical applications, like metasurfaces and plasmonics. The method is based on standard deposition, lithography and manipulation processes and can be applied to numerous material systems. Examples for modification of indium tin oxide and transition metal nitride layers are given.
CRIS-Team Scopus Importer:2025-02-04
Keywords: complex refractive index; ITO; material modification; nanooptics; TiN; ZrN